Elimination of hepatitis C virus infection in patients with haemophilia in Belgium: A single‐centre experience. Issue 6 (30th August 2019) - Fransen, Lennert; D'hondt, Pauline; Bielen, Rob; Van den Ende, Natalie; Robaeys, Geert; Peerlinck, Kathelijne; Nevens, Frederik
Abstract: Introduction: Patients with haemophilia are one of the subgroups with a high prevalence of hepatitis C virus (HCV) infection. They are a potential target group to eliminate HCV infection thanks to the availability of direct‐acting antiviral (DAA) therapy. Aim: To investigate the results of DAA therapy in a cohort of patients with bleeding disorders. Methods: This retrospective study was conducted between July 2018 and April 2019. All patients born before 1990 with haemophilia, von Willebrand factor Disease, factor V deficiency, factor VII deficiency or afibrinogenemia were included in this study. Results: Of 299 patients, 297 (99.3%) were tested for HCV antibody presence and 211 (71.0%) were positive. Of these, 205 (97.1%) were tested for HCV RNA and 153 (72.1%) were chronically infected. In total, 127 (83.0%) received antiviral therapy, and 110 (71.8%) patients were cured by antiviral treatment. The presence of cirrhosis was significantly higher in patients without a cure for HCV infection when compared to patients who achieved sustained virologic response by treatment or never infected (32.6% vs. 12.8% vs. 0%; P < .001). At the end of follow‐up in 2019, only 14 (9.1%) patients had a remaining HCV infection. Ten (71.4%) were lost to follow‐up, one (7.1%) patient refused, two (14.2%) had comorbidities and one (7.1%) will start treatment soon. Conclusion: In this cohort, the elimination targets for HCV infection in 2030 as proposed by the World Health Organization were already reached. Nevertheless, in order to cure every patient, monitoring tools are necessary.